1995
DOI: 10.1111/j.1439-0434.1995.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Potato Soft‐rot Resistance to Pectolytic Erwinia Species in a Tuber‐slice Assay

Abstract: Potato‐tuber slices and small tubers of 12 cultivars were inoculated with isolates of Erwinia carotovora subsp. atroseptica (Eca), E. c. subsp. carotovora (Ecc) and E. chrysanthemi (Ech). Cultivar resistance was expressed as the mean diameter of the rotted‐tissue area. Grouping of the cultivars into classes of relatively high, intermediate or low resistance, was different after incubation in air in comparison to incubation under anaerobic conditions, and depended on the (sub‐)species of bacteria used. When com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Tubers harvested from these plants were screened for tuber tissue resistance to Eta IPO 161 in a randomized block design under aerobic and anaerobic conditions according to the method for small tubers described by Allefs et al [2]. In short, 10 small tubers per transgenic clone or untransformed cultivar were cut twice tangentially at opposite sides and incubated overnight at 15 "C. A well, 4.0 mm deep and 5.0 mm in diameter, was pressed into the medullar tissue in which 20 ~1 1 x lo9 cfu/ml Eta was pipetted.…”
Section: Tpni Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tubers harvested from these plants were screened for tuber tissue resistance to Eta IPO 161 in a randomized block design under aerobic and anaerobic conditions according to the method for small tubers described by Allefs et al [2]. In short, 10 small tubers per transgenic clone or untransformed cultivar were cut twice tangentially at opposite sides and incubated overnight at 15 "C. A well, 4.0 mm deep and 5.0 mm in diameter, was pressed into the medullar tissue in which 20 ~1 1 x lo9 cfu/ml Eta was pipetted.…”
Section: Tpni Expression Analysismentioning
confidence: 99%
“…In short, 10 small tubers per transgenic clone or untransformed cultivar were cut twice tangentially at opposite sides and incubated overnight at 15 "C. A well, 4.0 mm deep and 5.0 mm in diameter, was pressed into the medullar tissue in which 20 ~1 1 x lo9 cfu/ml Eta was pipetted. Tubers were incubated at 20 "C for 3 days in nitrogen or 5 days in air as described [2]. After incubation, rotted tissue was scraped from the tubers and resistance expressed as the calculated mean diameter of the resulting cavity, measured at right angles.…”
Section: Tpni Expression Analysismentioning
confidence: 99%
“…After incubation, rotted tissue was carefully removed and the diameter of the lesion measured in two directions at right angles. Experimental layout and analysis of mean lesion diameters were as described by Allefs et al, 1995. Nine experiments were carried out for studying tuber tissue resistance. Experimental details of these experiments which were numbered from 1 to 9, are presented in Table 1.…”
Section: Tuber Tissue Resistancementioning
confidence: 99%
“…Since rotting of the mother tuber is an essential step during blackleg development [P6rombelon and Kelman, 1980], it was thought that selection for resistance to blackleg might be carried out by screening for tuber tissue resistance in the laboratory. Of the many methods published [see Allefs et al, 1995], the tuber slice inoculation method for screening of tuber tissue resistance as originally described by is one of the most extensively studied screening methods. It has been shown that for Erwinia carotovora subsp, atroseptica (Eca), E.c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation